Aldose Reductase (AR) Mediates and Perivascular Adipose Tissue (PVAT) Modulates Endothelial Dysfunction of Short-Term High-Fat Diet Feeding in Mice - Daniel J. Conklin; Petra Haberzettl; Kenneth G. MacKinlay; Daniel Murphy; Lexiao Jin; Fangping Yuan; Sanjay Srivastava; Aruni Bhatnagar (Metabolites, 2023)
Increased adiposity of both visceral and perivascular adipose tissue (PVAT) depots is associated with an increased risk of diabetes and cardiovascular disease (CVD). Under healthy conditions, PVAT modulates vascular tone via the release of PVAT-derived relaxing factors, including adiponectin and leptin. However, when PVAT expands with high-fat diet (HFD) feeding, it appears to contribute to the development of endothelial dysfunction (ED). Yet, the mechanisms by which PVAT alters vascular health are unclear. Aldose reductase (AR) catalyzes glucose reduction in the first step of the polyol pathway and has been long implicated in diabetic complications including neuropathy, retinopathy, nephropathy, and vascular diseases. To better understand the roles of both PVAT and AR in HFD-induced ED, we studied structural and functional changes in aortic PVAT induced by short-term HFD (60% kcal fat) feeding in wild type (WT) and aldose reductase-null (AR-null) mice. Although 4 weeks of HFD feeding significantly increased body fat and PVAT mass in both WT and AR-null mice, HFD feeding induced ED in the aortas of WT mice but not of AR-null mice. Moreover, HFD feeding augmented endothelial-dependent relaxation in aortas with intact PVAT only in WT and not in AR-null mice. These data indicate that AR mediates ED associated with short-term HFD feeding and that ED appears to provoke ‘compensatory changes’ in PVAT induced by HFD. As these data support that the ED of HFD feeding is AR-dependent, vascular-localized AR remains a potential target of temporally selective intervention.